Rethinking Technostress: The Moderating Role of Regulatory Focus in Enhancing Academic Performance among Accounting Students - Sriwidharmanely, Sriwidharmanely; Gultom, Maria Suniati (The Indonesian Journal of Accounting Research, 2025)
The study aims to elucidate the impact of technostress on student academic performance, with a focus on the moderating role of regulation-focused strategies (promotive and preventive regulatory focus). Specifically, it examines the correlation between academic performance and technostress among accounting students through the lens of regulatory focus theory. Data from 198 accounting students were analysed using a structural equation model. The findings show that technostress positively affects the academic performance of accounting students. Preventive regulatory focus negatively moderates the correlation between academic performance and technostress among accounting students. Moreover, a promotive regulatory focus enhances the correlation between their technostress and academic performance. This study's findings help clarify how technostress can positively influence students' academic performance. The results also enhance a model that boosts students' positive emotions, with implications for accounting student performance.